1987
DOI: 10.1128/mcb.7.5.1716
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of androgen-dependent and -independent expression of mouse sex-limited protein.

Abstract: Genes of the mouse S locus encoding C4 (the fourth component complement) and Slp (sex-limited protein) show extensive homology but are distinct in their function and regulation. In some mouse strains, such as B10.D2, Slp is androgen regulated, whereas in others, such as B10.W7R, expression of Slp is constitutive. We have previously shown that the B10.W7R strain has multiple Slp genes. In this report, we present the structure of the single C4 and four Slp genes of the B10.W7R S locus and compare the upstream fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

1988
1988
1993
1993

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…One of four B10.WR Slp genes, however, is more similar to the single androgendependent allele from B10.D2 mice; furthermore, an upstream region present in both of these Slp genes directed androgen-responsive transcription after transfection (35). In liver chromatin, hormone-responsive DNase-hypersensitive sites are located in the same upstream region, 2 kb from the Slp transcription start site (15), confirming its significance to expression in vivo.…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…One of four B10.WR Slp genes, however, is more similar to the single androgendependent allele from B10.D2 mice; furthermore, an upstream region present in both of these Slp genes directed androgen-responsive transcription after transfection (35). In liver chromatin, hormone-responsive DNase-hypersensitive sites are located in the same upstream region, 2 kb from the Slp transcription start site (15), confirming its significance to expression in vivo.…”
mentioning
confidence: 62%
“…While it may affect the Slp promoter, it does not appear to affect transcription from the upstream region (for instance, pG2.9RA5 lacked this domain but was not more active than pG2.9R). This and other elements may have some cell specificity, like the lysozyme gene negative element (36), since flanking DNA (in pG2.6 and pG2.9) allowed CAT expression in L cells (35) and HepG2 cells (23) but not in T47D cells. In G221 stable transformants, expression of pG2.9 was detectable, but it did not respond to hormone.…”
Section: Hormonal Regulation Of Mouse Sex-limited Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Information to date suggests that genetic elements within or near the structural gene play an important role (8,10,20,22,24,27). Several studies have indicated that androgen regulation of mouse mammary tumor virus expression is conferred by a sequence, termed the hormone response element, that is also responsible for progesterone and glucocorticoid regulation of virus transcription (10,24); this element is located upstream of the transcription initiation site and may be a binding site for the androgen receptor.…”
Section: Discussionmentioning
confidence: 99%